Treatment of partial thickness hand burn injuries in children with combination of silver foam dressing and zinc-hyaluronic gel: Case reports. Issue 13 (March 2018) - Jozsa, Gergo; Vajda, Peter; Garami, Andras; Csenkey, Alexandra; Juhasz, Zsolt
Abstract: Rationale: Burns is a common type of traumatic injury in childhood. Nowadays, several wound dressings are available to treat the second-degree hand burns conservatively. Patient concerns, diagnoses: At the authors' institute, 37 children were treated conservatively with a special dressing at first intervention containing Aquacel Ag foam and Zn-hyaluronic gel to determine their effectiveness on partial thickness hand burns. Interventions: The dressing was checked on the second day, and removed on the sixth or seventh day (unless it had spontaneously separated). Outcomes: None of the 37 children treated with this dressing were diagnosed with wound infection. The authors observed the epithelialization of the burned areas on the 6-7th day after primary conservative treatment. The dressing efficiently promotes epithelialization in all cases. Further advantage of Zn-hyaluronic gel is to enhance cell regeneration and inhibits dressing fixation into the wound. Lessons: Based on the authors' experience, with this special combination of wound dressing, a gentle, child-friendly, cost-effective treatment and excellent wound healing observed with favourable cosmetic results.